پهیوه ندییهكانی سلێمانی و كهركووك (١٩٣٢ -١٩١٨) - شوانى, ئاكۆ عبدالكه ریم محمود; عبدالرحمن, پشكۆ حه مه تاهیر (Sulaimani Journal for Humanities, 2021)
There is an old historic socio economic, political and military relationship between both sulaymaniyah and Kirkuk city, as they are two nearby Kurdish cities in the south of Kurdistan. This relationship was more thorough and stronger during Sheikh Mahmoods ruling period.People in Kirkuk were supporting sheikh Mahmood, he was always regarded Kirkuk as a Kurdish city and endeavored to bring it under his ruling power and never ready to forsake it. Also, there was a strong economic relationship between both cities as Kirkuk was always a place for trading and transporting all stuffs and goods from sulaymaniyah to the cities in the south of Iraq and vise versa.